Pendampingan Analisa Pasar Online pada Produk Asinan Buah “segeran.pwt” - Uswatun Khasanah; Feni Oktafiani; Tiara Misti Indriani; Dhanar Intan Surya Saputra (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The use of SWOT analysis (Strength, Weakness, Opportunities, Threats) and Business Model Canvas (BMC) was carried out on the pickled fruit product of “segeran.pwt”, which was made to know the effect of the use of SWOT analysis and the use of Business Model Canvas on the sale of the pickled fruit product of “segeran.pwt” in readiness for the online market. The methods used are the method of action and case studies. The results of SWOT analysis and Business Model Canvas are 1). By doing a SWOT analysis, you can find out the situation that will be faced or being faced and understand the strengths, weaknesses, opportunities, and threats in a business. 2). The use of the Business model canvas maximizes the performance generated by the startup.